2005
DOI: 10.1007/s11130-005-5097-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baking Process on Added Folic Acid and Endogenous Folates Stability in Wheat and Rye Breads

Abstract: In Poland bread as a staple food both made from wheat and rye flour can be a potential product for future fortification with folic acid. The objective of the study was to examine the effect of fermentation and baking on added folic acid and some endogenous folates stability during breadmaking of rye and wheat breads. Breads were produced using the formulation containing enriched flour with 0.2 mg folic acid/100 g product, baker's yeast and additionally ascorbic acid for wheat bread and lactic acid for rye brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 22 publications
7
32
0
7
Order By: Relevance
“…The Dutch and German beers also contained 5-methyltetrahydrofolate 10,12 , but folic acid only appeared in the German beer 10 . Folic acid is probably not a significant naturally occurring form of the vitamin in food, but it is often found in small quantities as an oxidation product of tetrahydrofolate 8 . Blakley 3 , in his work concerning the biochemistry of pteridines, reported that dihydrofolate and tetrahydrofolate were rapidly oxidized by air at neutral pH.…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch and German beers also contained 5-methyltetrahydrofolate 10,12 , but folic acid only appeared in the German beer 10 . Folic acid is probably not a significant naturally occurring form of the vitamin in food, but it is often found in small quantities as an oxidation product of tetrahydrofolate 8 . Blakley 3 , in his work concerning the biochemistry of pteridines, reported that dihydrofolate and tetrahydrofolate were rapidly oxidized by air at neutral pH.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of baking on the folic acid content was also studied with wheat and rye bread, and significant losses of folic acid in wheat (237 ± 7-184 ± 5) and rye breads (223 ± 9-158 ± 6) after baking were observed. They found that only the added folic acid content decreased but the endogenous one remained unchanged during baking (Gujska & Majewska 2005).…”
Section: Micronutrients Fortification: Unencapsulated Vs Microencapsmentioning
confidence: 99%
“…Apesar das farinhas de . Gujska e Majewska (2005) relataram o valor médio de 237 ± 7 µg.100 g -1 para a concentração desse nutriente, em farinhas encontradas em mercados da Polônia (o enriquecimento não é obrigatório). Recentemente, Sadighi et al (2008) avaliaram farinhas fortificadas com ferro no Irã e concluíram que 14% das amostras apresentaram quantidades aceitáveis do mineral, 74,4% continham quantidade adequada e em 11,6% foi observado teor de ferro abaixo do esperado.…”
Section: Cinzasunclassified